Synthesis and structure of new 4-amino-5-(2-R1-phenyl)-1,2,4-triazole-3-thiol alkilderivatives - Ye. S. Pruglo (Zaporozhye State Medical University, 2017)
Chemistry of heterocyclic systems is a separate branch of organic chemistry with a long history and future prospects. The ring system of 1,2,4-triazole continuously attracts the interest of chemists, pharmacologists and pharmacists in finding medicinal compounds through its universal potential interactions with biological systems. Today it is known that 1,2,4-triazole derivatives have antibacterial, antifungal, antiinflammatory, anticonvulsant, antiviral, antituberculosis, antioxidant, anticancer and antitumor activities. They also have analgesic, local anesthetic, antimalarial, antiproliferative effects, antihypertensive, antidepressant, sedative, antihistamine, hepatoprotective, hypoglycemic, diuretic, antipyretic and countless number of action types. Therefore, the search of biologically active remedies and creating of new drugs on its base is highly efficient topical issue of medical and pharmaceutical work. The purpose of these studies is the synthesis, establishment of physical-chemical parameters of new 4-amino-5-(2-R1-phenyl)-1,2,4-triazole-3-thiol alkylderivatives. Materials and methods. The studying of physical and chemical properties of compounds was made in accordance with the methods described in the State Pharmacopoeia of Ukraine 2.0. The melting point was determined on an automatic gear MPA100. The elemental composition of the compounds was set on the analyzer Elementar Vario EL cube. 1H NMR spectra were recorded using the spectrometer Varian Mercury VX-200 (1H, 200 MHz) and decrypted by a computer program SpinWorks 3.1.8. Chromatography-mass spectral studies were carried out in the gas-liquid chromatograph Agilent 1260 Infinity HPLC equipped with a mass spectrometer Agilent 6120 (in electrospray ionization (ESI)). Results. 4-amino-5-phenyl-4H-1,2,4-triazole-3-thiol and 4-amino-5-(2-bromophenyl)-4H-1,2,4-triazol-3-thiol were used as the initial materials. These compounds were obtained by reaction of benzoic acid hydrazide and 2-brombenzoic acid hydrazide with the excess of carbon disulfide in a solution of potassium hydroxide in butanol-1. In the future double excess of hydrazine hydrate was added to the synthesized products and mixture was heated for 3 hours. Then cooled and neutralized with hydrochloric acid. Thus the initial thiols were obtained. Individual peaks of derived compounds were established in carrying out the chromatography-mass spectral studies which correspond to theoretical calculations of atomic masses. Thus on the chromatogram of (5-(hexylthio)-3-phenyl-4H-1,2,4-triazole-4-amine, molecular weight 276,40) there are signals with m/z 277.1 and 279.1, which confirm the structure of obtained compound. Conclusions. 12 new alkylderivatives of 4-amino-5-(2-R1-phenyl)-1,2,4-triazole-3-thiol were synthesized in the result of the study. The structure of derived substances was confirmed by elemental analysis, 1H NMR spectroscopy and chromatography-mass spectrometry.